Analisis Kelayakan Ekonomi dan Lingkungan Pemanfaatan Sekam Padi sebagai Briket Biomassa - Aulia Annas Mufti; Mia Erpinda; Fuan Dini Artha Manulang (Dampak, 2026)
The potential of biomass energy in Indonesia has not been optimally utilized as a sustainable renewable energy alternative, while the use of biomass without processing has the potential to cause environmental impacts. One form of biomass processing that has potential is the production of briquettes using agricultural waste, including rice husks, which have generally only been burned. This study aims to analyze rice husk production and the environmental economic feasibility of its use as biomass briquettes. The methods used include field observations, interviews, and environmental economic feasibility analysis. The results of data collection show that Sumber Agung Village, Suoh District, West Lampung Regency produces 2.5 tons of rice husks per week from 10 rice mills that have been operating for 2–35 years. The feasibility analysis shows a net present value (NPV) of IDR 739,672,991.96, an interest rate of return (IRR) of 10.73%, and a benefit–cost ratio (BCR) of 1.09, indicating that the utilization of rice husks into briquettes is feasible. The results of this study are expected to serve as a basis for consideration in determining the form of sustainable utilization of agricultural waste, particularly rice husks.